History of origin of Russian medical and pharmaceutical terms - Samambetova Feruza Tolybaevna (Zien Journals, 2024)
This article is devoted to the history of the origin of Russian medical terminology. Most words are of Greek and Latin origin and are cosmopolitan. Despite this, Russian medical and pharmaceutical terminology contains many folk names of diseases, plants and medicines, as well as terminological groups formed by words of Old Slavonic and Old Russian origin
Keywords: Medical terminology; plants; diseases